The Struggle for Power in Post-Colonial Africa: Politics without Hegemony and the State. - Fadakinte, M. M. (Advances in Social Sciences Research Journal, 2020)
Scholars have explained the implications of colonization on Africa, but none has explained the implications to include crisis of hegemony and crisis of state. That is the thrust of this paper, an explanation of how/why post-colonial Africa got enmeshed in violent struggle for power by factions of the dominant class soon after independence. In Africa, colonialism imposed capitalism and inverted the process of evolving a capitalist sate, which made the emerging dominant class, who were of different ethnic and tribal origins, to develop into factions. As a result, the dominant classes were made up of belligerent factions and therefore cannot institute hegemonic process which will be the way they will maintain a dominant culture through the use of social institutions to formalize power. Consequently, in post-colonial Africa, politics is without hegemony (leadership, domination and control) and a state (institution for order). And whenever people struggle for power without hegemony and the state, what emerges is chaos. Hence, post-colonial African countries boil each time there is competition for power. Thus, there is need to redefine state-society relations in post-colonial Africa, based on a new paradigm of state formation that will reflect their colonial experience.